The intelligent entrepreneur : how the harvard business school graduates learned to 10 rules of successful business - Murphy, Bill (Virgin Books, 2010)
Tells how three HBS graduates turned down six-figure salaries at big corporations, bet on themselves and launched their own new companies. This title narrates a compelling and instructive story of how these three young founders developed ideas, assembled teams, built ventures, and achieved their dreams